On two species of Gymnomitrion (Gymnomitriaceae, Marchantiophyta) in the Eastern Sino-Himalaya - Bakalin, Vadim; Vilnet, Anna; Long, David; Klimova, Ksenia; Maltseva, Yulia; Nguyen, van Sinh; Ma, Wen Zhang (Phytotaxa, 2022)
Two Sino-Himalayan taxa of Gymnomitrion are reviewed, based on materials from South China and North Vietnam. Gymnomitrion sichuanicum is newly described from Sichuan Province of China and is characterized by the dioicous inflorescence, very short semi-crescentic leaf sinus and acute to obtuse leaf lobes. The habit of the species is superficially similar to Marsupella sprucei, but it differs in a number of features including perianth absence, dioicy, smaller leaf cells and distribution pattern. The genetically closely related Gymnomitrion africanum differs in its deeply gibbous sinus and rounded leaf lobes. Another taxon, Gymnomirion rubidum – still a poorly-known species, although described much earlier – is found to be genetically polymorphous with two defined haplotypes which are not easily distinguished morphologically; one of these is described as a new subspecies. The species is newly recorded from North Vietnam; collected in a degenerating relict Abies delavayi stand on a substrate very unusual for Gymnomitriaceae (decaying wood). Both taxa are described, discussed and supplemented with illustrations. These findings extend a series of similar records showing the great importance of the Eastern Sino-Himalaya and its surroundings in the survival of a unique complex of narrowly distributed montane taxa.